2016
DOI: 10.1111/hepr.12811
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B core‐related antigen kinetics in chronic hepatitis B virus genotype D‐infected patients treated with nucleos(t)ide analogues or pegylated‐interferon‐α

Abstract: Serum HBcrAg correlates with HBV DNA levels, most likely through expression of viral replication activity. We observed two different HBcrAg kinetics in NA-treated patients, suggesting different relapse risk related to NA cessation. Further studies on larger patient cohorts will elucidate the role of HBcrAg in the safe discontinuation of NA in CHB genotype D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For PEG‐IFN treatment, 2 studies exploring the decline of cccDNA and HBcrAg found conflicting results. While one study described a similar and significant decline of HBcrAg levels as cccDNA, the other study did not find a significant decline of HBcrAg with PEG‐IFN (Table ) . The number of patients in these 2 studies were too small (N = 58 and 8 respectively) to demonstrate any specific pattern of HBcrAg levels during PEG‐IFN therapy.…”
Section: Hbcrag and Anti‐viral Therapymentioning
confidence: 95%
“…For PEG‐IFN treatment, 2 studies exploring the decline of cccDNA and HBcrAg found conflicting results. While one study described a similar and significant decline of HBcrAg levels as cccDNA, the other study did not find a significant decline of HBcrAg with PEG‐IFN (Table ) . The number of patients in these 2 studies were too small (N = 58 and 8 respectively) to demonstrate any specific pattern of HBcrAg levels during PEG‐IFN therapy.…”
Section: Hbcrag and Anti‐viral Therapymentioning
confidence: 95%
“…Several reports have demonstrated that serum HBcrAg levels correlate with disease phases and reflect serum HBV DNA levels . In addition, baseline HBcrAg level has been shown to be associated with lamivudine resistance, viral relapse after lamivudine withdrawn, and response to pegylated‐interferon therapy . Previously, we have performed a study with 54 patients using a manual prototype of the HBcrAg assay and found that HBcrAg correlates well with cccDNA .…”
Section: Introductionmentioning
confidence: 97%
“…[16][17][18][19] In addition, baseline HBcrAg level has been shown to be associated with lamivudine resistance, viral relapse after lamivudine withdrawn, and response to pegylated-interferon therapy. [20][21][22][23][24][25] Previously, we have performed a study with 54 patients using a manual prototype of the HBcrAg assay and found that HBcrAg correlates well with cccDNA. 18 A more recent study with 57 patients has also demonstrated a good correlation between HBcrAg and cccDNA in the HBeAg-negative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Current nucleoside analogue (NA) therapies are able to efficiently suppress hepatitis B virus (HBV) replication. Current official guidelines recommend either entecavir or tenofovir disoproxil fumarate as first‐line NAs in CHB subjects owing to their potent HBV suppression with a minimal risk of drug resistance and a beneficial effect for the prevention of HCC development . However, these NAs cannot eliminate intrahepatic HBV covalently closed circular DNA (IH‐cccDNA) which persists in hepatocyte nuclei, resulting in difficulties for completely removing viruses .…”
Section: Introductionmentioning
confidence: 99%
“…Current official guidelines recommend either entecavir or tenofovir disoproxil fumarate as first-line NAs in CHB subjects owing to their potent HBV suppression with a minimal risk of drug resistance and a beneficial effect for the prevention of HCC development. [9][10][11][12][13][14] However, these NAs cannot eliminate intrahepatic HBV covalently closed circular DNA (IH-cccDNA) which persists in hepatocyte nuclei, resulting in difficulties for completely removing viruses. 15 As NAs are inhibitors for reverse transcriptase, they do not have direct efficacy on lowering IH-cccDNA levels.…”
Section: Introductionmentioning
confidence: 99%